تقييم خدمات الإعارة في المكتبات الجامعية : دراسة حالة في مكتبة الكلية التقنية الإدارية/بغداد - منى حازم يحيى (PROSPECTIVE RESEARCHES, 2023)
This research aims at evaluating the lending services in the library of the Managerial Technical College\ Baghdad. It inquired about the quality standards of the service and whether it satisfies the needs of the end users. The findings depended on the opinion of the end user’s point of view. The end users were the postgraduate and high studies students. A total sample of 171 users are gathered for this research from all the departments (Accounting, and Financial techniques, it Department, Comprehensive Quality Management, and Operation technique). 155 samples were postgraduate students, while another 16 were higher studies students. The researcher stated that there is a deficiency in the lending services, this deficiency was reflected through the dissatisfaction of the end users because of the lending period and\ or the number of items lent. The researcher also shed light on the fact that the lending procedures are not computerized. The study concluded a series of recommendations that are considered suitable for improving the service quality, facilitate the book search, and to make the user gets what he needs easily.